CHINA'S BELT AND ROAD INITIATIVE HEGEMONY STRATEGY IN BUILDING ALLIANCES IN INDO-PACIFIC - Martua Sitompul; Afrizal Hendra; Letjen Purn Dr. Wayan Midhio (CV. RADJA PUBLIKA, 2025)
This study analyzes how China's Belt and Road Initiative (BRI) is being used as a strategy to strengthen its hegemony in the Indo-Pacific region and challenge US dominance. Using descriptive qualitative methods that integrate literature analysis and case studies, the study explores the economic, political, and security impacts of the BRI in countries such as Indonesia, Pakistan, Sri Lanka, and the Philippines. The findings suggest that the BRI not only enhances connectivity and economic growth through massive investments in infrastructure, but also Building strong political alliances that shift geopolitical power dynamics in the region. For example, the Jakarta-Bandung high-speed rail project in Indonesia and the Hambantota port in Sri Lanka illustrate how BRI investments can improve local infrastructure. However, increasing economic dependence on China raises concerns about debt sustainability and the potential loss of sovereignty. national interests, such as in Sri Lanka, where a port had to be leased to China due to debt repayment. Furthermore, the BRI has strengthened military and strategic cooperation between China and partner countries, as seen in the China-Pakistan Economic Corridor (CPEC), which also supports Pakistan's military modernization. The proposed strategic recommendations include enhancing transparency and governance in BRI projects to mitigate concerns about corruption and mismanagement, addressing debt sustainability through mechanisms such as debt restructuring and grants, and balancing economic interests with environmental and social sustainability through rigorous impact assessments. With the right approach, the BRI has the potential to continue playing a significant role in global development and creating new opportunities for partner countries, while supporting regional stability and prosperity.